Heterogeneous expectations among professional forecasters - Conrad, Christian; Lahiri, Kajal (The Routledge handbook of economic expectations in historical perspective, 2025)
Macroeconomic expectations of various economic agents are characterized by substantial cross-sectional heterogeneity. This chapter focuses on heterogeneity in the expectations among professional forecasters, first presenting stylized facts and discussing theoretical explanations for heterogeneous expectations, before providing an overview of the empirical evidence supporting the different theories and pointing to possible directions for future research. A literature review is complemented by empirical evidence based on the Leibniz Centre for European Economic Research (ZEW) Financial Market Survey, covering the behavior of expectations heterogeneity during the recent surge in inflation in 2021 and 2022. A central finding is that differences in perceptions about the workings of the economy and heterogeneity in perceptions of the precision of new signals drive disagreement among professional forecasters. While the level of disagreement varies over the business cycle, differences in beliefs persist over time.
Gesehen am 15.01.2026